Indexing journal articles in the Medical Library - Kuak, M.S.J. (University of Malaya Library, 1985)
The medical library at the University of Malaya subscribes to 1,500 journal titles on medicine and related subjects. The collection includes all medical periodicals published in Malaysia and Singapore. Describes the history and processes of indexing all journal published in Malaysia and Singapore. The index also cover articles written by Malaysians in foreign journals. The aim of creating the index is to guide users to materils contained in journals as quickly as possible.